2022
DOI: 10.3389/fncel.2022.900725
|View full text |Cite
|
Sign up to set email alerts
|

UPR Responsive Genes Manf and Xbp1 in Stroke

Abstract: Stroke is a devastating medical condition with no treatment to hasten recovery. Its abrupt nature results in cataclysmic changes in the affected tissues. Resident cells fail to cope with the cellular stress resulting in massive cell death, which cannot be endogenously repaired. A potential strategy to improve stroke outcomes is to boost endogenous pro-survival pathways. The unfolded protein response (UPR), an evolutionarily conserved stress response, provides a promising opportunity to ameliorate the survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 145 publications
(289 reference statements)
0
11
0
Order By: Relevance
“…Other proteins with CXXC motifs found abundantly in the ER include protein disulfide isomerase (PDI) and reductase [ 17 ]. However, MANF does not show any PDI activity [ 18 ]. Strikingly, a mutation in the CXXC motif was shown to abolish MANF’s neuroprotective property.…”
Section: Structure-activity Relationship Of Manfmentioning
confidence: 99%
See 1 more Smart Citation
“…Other proteins with CXXC motifs found abundantly in the ER include protein disulfide isomerase (PDI) and reductase [ 17 ]. However, MANF does not show any PDI activity [ 18 ]. Strikingly, a mutation in the CXXC motif was shown to abolish MANF’s neuroprotective property.…”
Section: Structure-activity Relationship Of Manfmentioning
confidence: 99%
“…Stroke is one of the leading causes of disability in humans worldwide [ 18 ]. It is caused by local thrombosis or hemorrhage, leading to a lack of blood supply to the corresponding brain region, resulting in neuron death [ 52 ].…”
Section: Manf Signaling In Strokementioning
confidence: 99%
“…In quiescent cells, xbp1 transcripts are the most abundant and have the capability to repress around 15% of all yeast genes as the cells transition into the quiescent state. It is also important Numerous studies in higher eukaryotes have revealed the induction or detection of xbp1 expression in various types of cancer cells 67 , as well as in conditions such as stroke 68 and neurodegenerative diseases, including Alzheimer's disease 69 . The overexpression of xbp1 has demonstrated certain advantageous effects in the aging of the mammalian brain 69,70 .…”
Section: Epigenetic Responsesmentioning
confidence: 99%
“…CDNF is a vertebrate-specific paralog of MANF (12). In cells, CDNF and MANF localize in the endoplasmic reticulum (ER) (19,20), where they regulate protein homeostasis and ER stress-induced unfolded protein response (UPR) signaling (21)(22)(23)(24)(25). As a potential therapeutic factor for dopamine neurons, CDNF was tested in Phase I-II clinical trials in 17 PD patients, where it was shown to be safe and well tolerated (26,27).…”
Section: Introductionmentioning
confidence: 99%